1836 Mass. Rev. Stat. 750, ch. 134, § 16 - (:unkn) unknown (My University, 1835)
Prohibited the carry of a dirk, dagger, sword, pistol, or other offensive and dangerous weapon without reasonable cause to fear assault, injury, or violence to oneself, their family, or property. Violators required to post a surety not exceeding six months.
Keywords: CARRY; GOING ARMED; SURETY